2019
DOI: 10.3892/ol.2019.10638
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‑induced DNA methylation in the white blood cells of patients with colorectal cancer

Abstract: The secretions of cancer cells alter epigenetic regulation in cancer stromal cells. The present study investigated the methylation changes in white blood cells (WBCs) caused by the secretions of colorectal cancer (CRC) cells. Changes in the DNA methylation of peripheral blood mononuclear cells (PBMCs) from normal individuals co-cultured with CRC cells were estimated using a methylation microarray. These changes were then compared against the DNA methylation changes and mRNA levels observed in the WBCs of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Previous studies from our group reported paracrine signal-induced PBMC gene upregulation in various cancer types through epigenetic regulation (4,16,17). On the basis of paracrine signal-induced PBMC gene upregulation, we explored the possibility to use protein expression on circulating T-lymphocytes as a biomarker to discriminate early-stage NSCLC and healthy individuals by automated ow cytometry analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies from our group reported paracrine signal-induced PBMC gene upregulation in various cancer types through epigenetic regulation (4,16,17). On the basis of paracrine signal-induced PBMC gene upregulation, we explored the possibility to use protein expression on circulating T-lymphocytes as a biomarker to discriminate early-stage NSCLC and healthy individuals by automated ow cytometry analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of immune-related molecules on peripheral blood mononuclear cell (PBMC) is considered to play a role in antitumor activity. The changes of gene expression pro ling in PBMC seem to represent the host's response to the cancer cells via paracrine signal (4). Several studies have shown that the characterization of gene expression in PBMC may be useful as a diagnostic or for early detection (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…bladder cancer [33][34][35][36]. Moreover, previous research has presented that the expression PLOD1 can be predicted prognosis of IDH mut glioma patients, which involved in oxygen metabolism [37].…”
Section: Plos Onementioning
confidence: 99%
“…PLOD1 has been reported that its aberrant expression level was signi cantly correlated with various human cancers, including prostate cancer, gastric cancer, colorectal cancer and bladder cancer [32][33][34][35].…”
Section: Disccussionmentioning
confidence: 99%